Competency, Organizational Health, Job Career, Job Performance And Employees Turnover - I Made Hadi Purnantara; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2015)
This research objective is investigate the influences among competency,organizational hygiene factor, career scaffold, employees’ job performance and employees’turnover intentions in The Seminyak Beach Resort & Spa. A survey was conducted among asample of 242 employees at the Seminyak Beach Resort & Spa through purposive sampledwith bipolar adjective scale questionnaire but only 189 qualified respondent data could betabulated, those were analyzed using Structural Equation Modeling via AMOS 22.0.According the result of the analysis, competency had positive and significantinfluence toward employees’ job performance (? = 0,228, CR = 2,759, ? =0,006) but it hadnegative influence toward career scaffold (? = -0,141, CR = -2,123, ? =0,034). Otherwise,organizational hygiene factor able to give positive influence toward career scaffold (? =0,840, CR =8,705, ? =***) and employees’ job performance (? = 0,206, CR =1,133, ? =0,257) but it had negative influence on employees’ turnover intentions (? = -0,162, CR = -0,914, ? =0,361). Also career scaffold as intervening variable able to give positive andsignificant influence for both employees’ job performance (? = 0,555, CR =2,919, ? =0,004)and employees’ turnover intentions (? = 0,605, CR =2,938, ? =0,003). In the meantime,employees’ job performance had positive and significant influence toward employees’turnover intentions (? = 0,492, CR =3,516, ? =***).The Research limitations/implications – Limitations in this research showed otheroutside factor still giving influence and it might be able to add more variables for nextresearch. Practical implications – The findings provide for a better understanding of howorganizational hygiene factor can control employees’ turnover intention and it as a trigger toboost employees’ job performance through career scaffold.Keyword : Competency, Organizational Hygiene Factor, Career Scaffold, Employees’ JobPerformance And Employees’ Turnover Intentions